(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Inguinal hernia repair, a globally common procedure, has shifted its focus from minimizing recurrence to mitigating Chronic Postoperative Inguinal Pain (CPIP) and preserving the intricate neurovascular structures of the spermatic cord (SC). CPIP and reproductive system compromise, often stemming from surgical trauma, nerve entrapment, or mesh-induced inflammation, necessitate innovative strategies that prioritize SC integrity. This comprehensive review evaluates advancements across surgical approach, material science, and regenerative medicine designed to improve patient quality of life. Analysis confirms that minimally invasive laparoscopic approaches (TAPP and TEP) consistently yield lower chronic pain rates than open mesh repair, primarily by reducing tissue trauma and dissection of the SC. Material innovations focus on lightweight and three-dimensional meshes, along with the adoption of atraumatic fixation techniques, such as bio-adhesives or non-fixation, to prevent nerve and cord compression. The most precise cord-sparing innovation is microsurgically assisted hernia repair, which uses high magnification for meticulous anatomical preservation, demonstrating superior outcomes regarding pain and vas deferens injury. Emerging regenerative techniques include using biocompatible barrier membranes to shield the SC from the inflammatory effects of synthetic mesh, as well as developing dynamic scaffolds designed to promote de novo formation of muscle and nerve tissue, moving away from simple fibrotic reinforcement. Although conventional synthetic mesh remains the standard due to high recurrence rates associated with current biological materials, future perspectives necessitate robust clinical validation of these precision and regenerative methodologies to firmly establish truly cord-sparing hernioplasty standards.